Keratitis–ichthyosis–deafness syndrome: first affected family reported in the Middle East - Al Fahaad H (International Medical Case Reports Journal, 2014)
Hamad Al FahaadDepartment of Dermatology, College of Medicine, Najran University, Najran, Saudi ArabiaIntroduction: Keratitis–ichthyosis–deafness (KID) syndrome is a rare congenital multisystem disorder affecting certain tissues of ectodermal origin such as epidermis, cochlea, and cornea, leading mainly to palmoplantar hyperkeratosis, ichthyosiform scaling, deafness, and blindness. The author reports for the first time in the Middle East three family members suffering from KID syndrome in the southwestern part of Saudi Arabia.Case presentation: Three patients from one family (ages 26, 16, and 14 years) of apparently normal parents, with the two eldest being females and the youngest being male. All three patients were referred from a peripheral hospital to our dermatology clinic due to recurrent cutaneous fungal infections on their trunk, forearms, legs, and nails. On full assessment, they also found to have nearly similar cutaneous problems manifested by palmoplantar hyperkeratosis, generalized ichthyosiform scaling, subungual hyperkeratosis, and nail dystrophies. All patients suffered from total hearing loss in both ears since childhood as confirmed by pure tune audiometry. However, there was no blindness in any case; blepharitis with marked photophobia was the only ocular complaint. All these features are classically suggestive of KID syndrome.Keywords: connexin 26, GJB2, ichthyosis, KID syndrome, palmoplantar hyperkeratosis